2015
DOI: 10.1111/ijs.12430
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Inflammation Assessed with 18F-FDG PET/CT is Higher in Symptomatic Compared with Asymptomatic Patients

Abstract: (18)F-FDG uptake on PET/CT correlated with histological assessments of inflammation and was higher in patients with symptomatic compared with asymptomatic carotid artery plaques. These results support the use of (18)F-FDG PET/CT in the detection inflammation in carotid atherosclerosis, which may be of help in the detection of vulnerable plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…We know that excised plaques both shrink 17 and may be partly damaged. 17,25 The strength of our study was the close timing between the PET examinations and the endarterectomies. Our study patients had plaques not only presumed highly inflammatory giving recent symptoms, but also plaques removed prophylactically from asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We know that excised plaques both shrink 17 and may be partly damaged. 17,25 The strength of our study was the close timing between the PET examinations and the endarterectomies. Our study patients had plaques not only presumed highly inflammatory giving recent symptoms, but also plaques removed prophylactically from asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…assessment on selected sections from this study cohort and found that the amount of inflammatory cells was in the same 5% category at both assessments for 73% of the sections (Kappa = 0.73). 25 The amount of inflammation per plaque was 6.8% (SD 4.0; range 0.4-17.9).…”
Section: Endarterectomy and Histological Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…One study assessed 18-FDG uptake vs. histology (r = 0.521, p = 0.003) [32] and showed that the SUV was signifi cantly higher in symptomatic (1.75) vs. asymptomatic (1.43) patients. Oxidized (ox) LDL has been shown to increase F-18-FDG uptake and glycolytic metabolism by more than an order of magnitude via the upregulation of GLUT1 expression and hexokinase activity [33,34].…”
Section: F-18-fdg Uptake At the Cellular Levelmentioning
confidence: 99%
“…In this line, Figueroa et al followed 513 patients without symptomatic cardiovascular disease for a mean of 4.2 years, and found that 18 F-FDG uptake within the wall of the ascending aorta was an independent predictor of future cardiovascular events [9]. The carotid plaque inflammation, as measured by 18 F-FDG PET and correlated with the degree of macrophage infiltration and plaque erosion [10], has been also associated with a high risk of early stroke recurrence, independently of the degree of stenosis [11], and may, thus, be a useful imaging biomarker for high-risk carotid plaque [10,12], especially in case of imminent vascular event [11,13], and for yet symptomatic plaques [14].…”
mentioning
confidence: 99%